Biliopancreatic Diversion With Duodenal Switch. Long Term Weight Loss - Toni Stoyanov; Pedro Sanchez; Antonio Calero; Augustina Moreno; Emilio Blazquez; Servando Rebollo (Journal of Biomedical & Clinical Research, 2015)
Biliopancreatic derivation with duodenal switch (BPDDS) as an operative technique in the management of morbid obesity was created as an alternative to BPD (Scopinaro's operation), because of BPD-DS's fewer malabsorption side effects, better restrictive effect to the stomach remnant, fewer peptic ulcers and dumping syndromes, as well as lower morbidity and mortality rate. Between January 2003 and June 2012 in the University Hospital Center of Albacete, 141 patients with morbid obesity underwent BPD-DS. The patients were divided in groups according to four criteria: length of the common channel, age, gender and initial Body Mass Index. On the 6th postoperative year in our study the percent of excessive body weight loss was 67.6% and the percentage of excessive BMI loss was 73%. According to the evaluation announced by Hess D.S. & Hess D.W, our results could be assessed as successful after 6 months, good on the first year, excellent on the second, and good from 3rd to 9th postoperative years. Our results confirm the hypothesis that the biliopancreatic derivation with duodenal switch is a bariatric intervention, which leads to a significant weight loss, well preserved in time.